2022
DOI: 10.3389/fneur.2022.868137
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment Plasma D-Dimer Levels Are Associated With Short-Term Outcomes in Patients With Cancer-Associated Stroke

Abstract: Background and ObjectiveHypercoagulability is associated with increased risks of ischemic stroke and subsequent mortality in patients with active cancer. This study investigated the relationships between plasma D-dimer levels after stroke treatment and short-term outcomes in patients with cancer-associated stroke.MethodsThis retrospective, observational, multicenter study analyzed consecutive patients with cancer-associated ischemic stroke. Hypercoagulability was assessed by plasma D-dimer levels before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A previous meta‐analysis demonstrated that DD levels predicted in‐hospital mortality in patients with stroke 9 . Moreover, DD level was reported to predict 30‐day mortality in cancer patients who developed CI 10,11 . In this study, NSCLC patients with high DD levels had a significantly shorter survival period after incident CI than those with low DD levels.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A previous meta‐analysis demonstrated that DD levels predicted in‐hospital mortality in patients with stroke 9 . Moreover, DD level was reported to predict 30‐day mortality in cancer patients who developed CI 10,11 . In this study, NSCLC patients with high DD levels had a significantly shorter survival period after incident CI than those with low DD levels.…”
Section: Discussionmentioning
confidence: 47%
“…9 Moreover, DD level was reported to predict 30day mortality in cancer patients who developed CI. 10,11 In this study, NSCLC patients with high DD levels had a significantly shorter survival period after incident CI than those with low DD levels. This is the first study to demonstrate the significance of the DD level as a potential prognostic predictor in advanced NSCLC patients who develop symptomatic CI.…”
Section: Discussionmentioning
confidence: 55%
“…The main treatment methods for acute cerebral infarction are thrombolytic, anticoagulation and antiplatelet aggregation therapies. Previous studies have shown that direct oral anticoagulants significantly decrease the risk of cancer‐associated thrombosis recurrence, 17 and anticoagulation therapy might prevent the recurrence of cancer‐associated stroke 18 and can improve its short‐term prognosis 15,19 . There have also been studies comparing antiplatelet and oral anticoagulant therapy to prevent recurrence in tumor patients with cerebral infarction; however, there was no significant difference between the two methods, but the aspirin group was found to have a lower risk of bleeding than with oral rivaroxaban anticoagulant therapy 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that direct oral anticoagulants significantly decrease the risk of cancer‐associated thrombosis recurrence, 17 and anticoagulation therapy might prevent the recurrence of cancer‐associated stroke 18 and can improve its short‐term prognosis. 15 , 19 There have also been studies comparing antiplatelet and oral anticoagulant therapy to prevent recurrence in tumor patients with cerebral infarction; however, there was no significant difference between the two methods, but the aspirin group was found to have a lower risk of bleeding than with oral rivaroxaban anticoagulant therapy. 20 However, our study showed no significant difference among the three treatments, although this may be related to the relatively few patients who received thrombolytic and anticoagulant therapy in our dataset.…”
Section: Discussionmentioning
confidence: 99%
“…A three to four-fold increase in plasma D-dimer is related to a poor disease prognosis [28]. An elevation in D-dimer levels is also noted in COVID-19 cases, reflecting underlying conditions, such as cancer, diabetes, stroke, and pregnancy [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%